PENGEMBANGAN MEDIA POP-UP BOOK BERBASIS PJBL (PROJECT BASED LEARNING) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK KELAS III MI YATABU - Atikah; Deni Adi Putra; Meirza Nanda Faradita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to develop learning media in the form of pop-up books that focus on alphabet material and PJBL-based learning methods to improve students’ creative thinking skills in Indonesian Language subjects Chapter I: Let’s Play! in grade III of elementary school. This study used the Four D (4D) development model which includes four stages: Define, Design, Develop, and Disseminate. The results of the study indicated that this pop-up book learning media can be categorized as feasible. The results were obtained through the validation process by the validator using a validation sheet and a feasibility test by the research subject using a questionnaire response sheet. The percentage of values given by material experts is 96% with the criteria “Very Valid”, the results of the assessment by media experts are 95% with the criteria “Very Valid.” While the results of the student response questionnaire assessment are 88% with the category “Very Practical,” and the results of the teacher’s warm response data processing are 97% with the category “Very Practical.” Learning media is also effective to use with a classical completeness percentage obtained of 85% with the category “Very Effective.” Therefore, it is obtained that the pop-up book alphabet learning media (Chapter 1: Let’s Play) Based on PJBL class III MI Yatabu has been categorized as feasible and can be used to improve creative thinking skills, especially for Indonesian language subject, alphabet material, chapter 1: Let’s Play!.